Project-specific constraints influencing productivity of tradespeople in the Nigerian construction industry. Issue 1 (9th October 2019) - Ugulu, Rex Asibuodu; Arewa, Andrew; Allen, Stephen
Abstract : Purpose: The purpose of this paper is to establish the perception of tradespeople about project-specific constraints (PSCs) influencing construction productivity in Nigeria. Design/methodology/approach: Using a qualitative descriptive survey comprising face-to-face semi-structured interviews and a purposive sampling method, views of eight groups of tradespeople and seven project managers on live construction projects in Nigeria were collected. The study used conventional content analysis with the aid of NVivo 12 pro computer software for the analysis. Findings: The research evaluated the PSCs and their effect on construction productivity of tradespeople. The findings identified five key PSCs, namely: lack of promotions/reward system, unsafe/poor health condition of workers, delay in material availability, inadequate site amenities and an ageing workforce. These results support earlier research on constraints influencing labour productivity, however, the poor health condition of workers and material unavailability appear to be more unique when compared to other previous studies. Research limitations/implications: The study focussed on the Federal Capital Territory Abuja and the Lagos State of Nigeria. It provides insight into the PSCs influencing the productivity of tradespeople in the Nigerian construction industry. Further research to identify the PSCs in depth, in the Eastern part of Nigeria is necessary. Practical implications: The PSCs influencing tradespeople's productivity was identified. The level of the relative impact of the PSCs is expected to guide the project team in addressing the PSCs in a method that is cost effective. Originality/value: This study is original research that has underlined some areas of improvement in construction project performance.